Влияние конструктивных и эксплуатационных параметров стволов установок импульсного пожаротушения на гидродинамические характеристики истечения жидкости - Ivanitskiy, Александр (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2008)
In this article results of studying hydrodynamical characteristics of FPI trunks are presented. These results are based on mathematical modeling and experimental researches of hydrodynamical characteristics of the discharge of a liquid from trunk СП-И УИП-1.